Context-Based Aesthetic Reflections of Collective Creativity in Turkish Culture: Dialogue Folk Songs of the Malatya Region - Kurt, Begüm (Fırat University, 2022)
Reciprocal poetry is one of the continuous forms of expression of an ancient tradition in Turkish oral culture. In different cultures, in similar productions; examples seen in the conversations of people who represent work-relationships such as poets, shepherds, lovers, mother-daughter, bride-mother-in-law, or two material elements that usually emphasize abstract concepts by amateur/professional creators in impromptu/non-immediate forms in different performance environments shows that it is one of the common forms of culture. Uses that can be considered as expression form and discourse style are an important choice in creating literary products and have an intense use. Emotions and thoughts should be transformed into literary products in a behavioral field of action and exhibited in the presence of society, and culture, space, society and human factors should be examined from an integrated perspective as complementary elements. This study, which is limited to the folk song tradition of the Malatya region and the folk songs sung mutually belonging to the region, includes the culture-human-geography relationship. Written sources were scanned in order to evaluate the situation of mutual folk songs whose performances faded in the oral tradition; The obtained folk song texts were examined in terms of their reasons, functions and stylistic features with the content analysis method. Local folk songs that exhibit a part of the national tradition; quantitatively in abundance, qualitatively with its flavors, it has been passed on through generations and has existed without losing its function. In the tradition of singing Turkish, it has been determined that mutual, bickering, question-answer, and dialogic folk songs have remarkable functions and local performance styles.

Karşılıklı şiir söyleme Türk sözlü kültüründe kadim bir geleneğin süreklilik göstermiş ifade biçimlerindendir. Farklı kültürlerde, benzer tarzda üretimlerde; irticali/irticali olmayan biçimlerde, amatör/profesyonel yaratıcılarca değişik icra ortamlarında şair, çoban, sevgili, anne-kız, gelin-kayınvalide gibi iş-ilişki temsili sunan kişilerin veya genellikle soyut kavramlara vurgu yapan iki maddi unsurun söyleşilerinde görülen örnekler, diyaloglu şiirlerin, dünya kültürünün müşterek formlarından biri olduğunu göstermektedir. İfade formu ve söylem stili olarak kabul edilebilecek kullanımlar, edebi ürünleri oluşturmada önemli bir tercihtir ve yoğun bir kullanıma sahiptir. Duygu ve düşüncelerin davranışsal bir eylem alanı içinde edebi ürünlere dönüştürülerek toplum huzurunda teşhir edilmesi ve kültür, mekân, toplum, insan faktörlerinin birbirini tamamlayan unsurlar olarak tümleşik bir bakış açısıyla irdelenmesi gerekmektedir. Malatya yöresi türkü söyleme geleneği ve yöreye ait karşılıklı söylenmiş türkülerle sınırlandırılan bu çalışma, kültür-insan-coğrafya ilişkisini içermektedir. Sözlü gelenek içerisinde icraları sönükleşen karşılıklı türkülerin durum değerlendirmesini yapabilmek için yazılı kaynaklar taranmış; elde edilen türkü metinleri içerik çözümleme metoduyla söylenme sebepleri, işlevleri ve üslup özellikleri bakımından irdelenmiştir. Millî geleneğin bir parçasını sergileyen yöreye ait türküler; niceliksel bakımdan ganiliği, niteliksel açıdan çeşnileriyle nesiller boyu aktarılmış, işlevini yitirmeden var olmuştur. Türkü söyleme geleneği içerisinde ise karşılıklı, atışmalı, soru-cevaplı, diyaloglu türkülerin dikkat çekici işlevleri ve yöreye özgü icra biçimleri olduğu tespit edilmiştir.
TÜRK KÜLTÜRÜNDE KOLEKTİF YARATICILIĞIN BAĞLAM TEMELLİ ESTETİK YANSIMALARI: MALATYA YÖRESİ DİYALOGLU TÜRKÜLERİ